Development and evaluation of a method to quantify rugby place kick performance from initial ball flight data - Atack, A.; Trewartha, G.; Bezodis, N. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to develop and evaluate a method for quantifying rugby place kick performance using a metric that represents field-based performance but relies only on data typically available within a laboratory setting. A mathematical model was developed to predict the flight path of a rugby ball using equations of projectile motion and initial ball flight kinematics as inputs. The accuracy of the model predictions were then evaluated against empirical data collected from eight place kicks taken 22 m from the goalposts on a rugby pitch. The model estimated the position of the ball at the instant it reached the goalposts with a root mean square error of 0.65 m (2.9% of the range). It is intended that this method will provide an applied outcome measure that is relevant to players and coaches.